Social Representations of the Curriculum in Physical Education Teachers: A Multi-Method Analysis regarding Teachers from Copacabana, Colombia - González Ramírez, Roger Alexander; González Palacio, Enoc Valentin (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to provide a specific analysis of social representations on the curriculum in physical education teachers. Materials and methods. The study focuses on a sample of 25 physical education teachers from Copacabana, Antioquia, using a multi-method approach with a predominance of grounded theory. Data were collected through in-depth interviews, sociodemographic surveys, and natural semantic networks. Results. Qualitative analysis using ATLAS.ti revealed four emerging categories in this group: dynamic and situated curriculum, curriculum for comprehensive training, flexible and contextualized curriculum, and prescriptive curriculum. Quantitative analysis identified a central core of representation composed of concepts such as planning, instructions, and education. The results indicate that physical education teachers conceive the curriculum in a multidimensional way, reflecting the particularities of their discipline. A tension is observed between adherence to prescriptive curricular structures and the need for flexibility to address the specific demands of physical education. Conclusions. The study concludes that these representations are strongly influenced by the practical context of teaching physical education, suggesting the need for curricular approaches adapted to this area.